2010
DOI: 10.1007/s00467-010-1509-y
|View full text |Cite
|
Sign up to set email alerts
|

Aortic stiffness in ESRD children before and after renal transplantation

Abstract: Cardiovascular complications are the main cause of death in end-stage renal failure in adult patients, but those complications start in childhood. Renal transplantation (RT) seems to reduce or even reverse certain abnormalities seen in dialyzed patients. Since RT seems to correct metabolic abnormalities that play a role in cardiovascular disease, aortic pulse wave velocity (APWV) was used to evaluate aortic stiffness before and after RT. We included 15 children on chronic hemodialysis (HD), aged 11.1 +/- 4.8 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 34 publications
1
14
1
1
Order By: Relevance
“…Our study is also larger and included patients that were relatively older. As the prevalence of aortic stiffness increases with age, previous studies that have included fewer patients, and especially younger patients, might have lacked sufficient power to detect a BP-independent reduction in c-f PWV [26]. In the general population, McEniery et al [12] showed that age-related increase in aortic stiffness was steeper after the fifth decade and, therefore, suggested that aortic PWV is a more sensitive marker of vascular aging after the fifth decade.…”
Section: Discussionmentioning
confidence: 97%
“…Our study is also larger and included patients that were relatively older. As the prevalence of aortic stiffness increases with age, previous studies that have included fewer patients, and especially younger patients, might have lacked sufficient power to detect a BP-independent reduction in c-f PWV [26]. In the general population, McEniery et al [12] showed that age-related increase in aortic stiffness was steeper after the fifth decade and, therefore, suggested that aortic PWV is a more sensitive marker of vascular aging after the fifth decade.…”
Section: Discussionmentioning
confidence: 97%
“…One study found little improvement before and after the initiation of hemodialysis, suggesting that structural as opposed to functional changes are responsible for increased arterial stiffness in this group [47]. Other pediatric studies have found lower cfPWV and AIx after renal transplantation, suggesting that transplantation can improve the arteriopathy associated with CKD [48,49,50]. While cfPWV tends to improve after renal transplantation, there is disagreement as to whether there is a difference between the cfPWV of patients with a functioning graft versus healthy controls [48,49,51,52].…”
Section: Conditions Associated With Arterial Stiffnessmentioning
confidence: 99%
“…Other pediatric studies have found lower cfPWV and AIx after renal transplantation, suggesting that transplantation can improve the arteriopathy associated with CKD [48,49,50]. While cfPWV tends to improve after renal transplantation, there is disagreement as to whether there is a difference between the cfPWV of patients with a functioning graft versus healthy controls [48,49,51,52]. Hypertension is a risk factor for increased AIx in children with glomerulopathies, which was also higher compared to a healthy comparison group [53].…”
Section: Conditions Associated With Arterial Stiffnessmentioning
confidence: 99%
“…In donors and recipients, it was associated with a cluster of cardiovascular risk factors including smoking habits, plasma glucose, and renal factors reflecting nephron mass (eg, time since nephrectomy, age in donors, and rejection in recipients). More recently, pulse wave velocity, in addition to proteinuria and systolic blood pressure, has been reported to be an independent predictor of the rate of decline in renal function in chronic kidney disease patients, 15 and in pediatric 62 and adult kidney transplant recipients. 56,58 While recognizing the likely dual causality between aortic stiffness and renal failure, these observations provide further evidence that atherosclerosis and the resulting arterial stiffness play a pathogenic role in renal function decline.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] It represents a strong predictor of renal and patient cardiovascular outcomes 1,3,5,6,8,[11][12][13]15,17,35,56,58,[60][61][62][63] ( Figure 2). Therefore, posttransplant hypertension represents a multipathogenic process that amplifies a vicious cycle where allograft and cardiovascular outcomes in kidney transplant recipients are determined by the interaction of 2 distinct donor and recipient genetic make-ups, and the inherited cardiovascular and renal risk factors from earlier phases and new recipient and donor-related environmental and demographic variables that may occur during implantation and posttransplant (Figure 1).…”
Section: Introductionmentioning
confidence: 99%